2013
DOI: 10.1093/humrep/det434
|View full text |Cite
|
Sign up to set email alerts
|

Proposed legislative change mandating retrospective release of identifying information: consultation with donors and Government response

Abstract: STUDY QUESTIONHow do gamete donors who presumed they could remain anonymous respond to proposed legislation to retrospectively remove anonymity?SUMMARY ANSWERA little more than half of the donors opposed the recommendation to introduce legislation to remove donor anonymity with retrospective effect.WHAT IS KNOWN ALREADYAn increasing proportion of parents disclose their origins to their donor-conceived children and growing numbers of donor-conceived adults are aware of how they were conceived. Research indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Consistent with Australian research investigating the varying perspectives and experiences of donors, recipients and donor offspring (Rodino et al, 2011;Allan, 2012b;Hammarberg et al, 2014), information provided by expert counsellors in our study further supported the importance of an established specialist-based intermediary service dedicated to providing all stakeholders of a donor-assisted conception programme, information and support on sensitive matters of consent, release of information, contact ramifi cations and ongoing support.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with Australian research investigating the varying perspectives and experiences of donors, recipients and donor offspring (Rodino et al, 2011;Allan, 2012b;Hammarberg et al, 2014), information provided by expert counsellors in our study further supported the importance of an established specialist-based intermediary service dedicated to providing all stakeholders of a donor-assisted conception programme, information and support on sensitive matters of consent, release of information, contact ramifi cations and ongoing support.…”
Section: Discussionsupporting
confidence: 86%
“…Participants were cognizant of a child's rights to genetic heritage with a philosophy valuing transparency, honesty, and identity needs for the donor-conceived child and recognizing a child's right to disclosure about circumstances of conception and to biological knowledge. The results of this study are congruent with other studies showing that prospective recipient parents have donor information needs, including knowledge of biological lineage for their children (49)(50)(51) with an increasing proportion of recipient parents now wanting to disclose circumstances of conception (52). Whether donor information exchange needs can be reliably fulfilled through international CBRC donor conception programs, however, has not been put to the empirical test.…”
Section: Discussionsupporting
confidence: 82%
“…First, the compromise, while giving some attention to donor rights, does not go far enough to satisfy the majority of donors. A study conducted before the introduction of the new legislation indicated that the most donors were opposed to the change 10 . Many have suggested other options, such as voluntary disclosure of information by donors to a central registry.…”
Section: Shortcomings Of the Victorian Modelmentioning
confidence: 99%
“…6,7 While evidence suggests that donor-conceived children are as psychologically healthy as children conceived by natural means, 8 there is, nevertheless, an undeniable desire felt by many donor-conceived children to know their biological heritage. [9][10][11][12] Underlying this desire are the identity formation processes of the donor child, which in some way have been adversely affected or frustrated by the mystery surrounding their biological originsa phenomenon often described as genealogical bewilderment. 6 What donor children articulate in their personal narratives is a social and existential view of the passage of genetic materialsomething far more than a physiological phenomenon.…”
Section: The Rights Of Donor Children Versus Those Of Donor Parentsmentioning
confidence: 99%
See 1 more Smart Citation